A comparison of magnetic overshoots at the bow shocks of Mercury and Saturn. Issue 7 (25th July 2013) - Masters, A.; Slavin, J. A.; DiBraccio, G. A.; Sundberg, T.; Winslow, R. M.; Johnson, C. L.; Anderson, B. J.; Korth, H.
Abstract : [1] The MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) spacecraft at Mercury and the Cassini spacecraft at Saturn provide us with orbiters around planets at more diverse heliocentric distances than ever before. The dramatically different solar wind conditions at these two planets should mean that Mercury's bow shock is considerably weaker (lower Mach numbers) than Saturn's bow shock. This is expected to produce different magnetic overshoot amplitudes at each bow shock, because the Relative Overshoot Amplitude (ROA) has been shown to increase with both fast magnetosonic Mach number and upstream plasma β . We qualitatively compare the parameter regimes of Mercury's and Saturn's bow shock by determining ROAs. We analyze 133 MESSENGER encounters with Mercury's bow shock and 90 Cassini encounters with Saturn's bow shock, all with a clear shock ramp. At five of the 133 Mercury bow shock encounters, there is no resolvable magnetic overshoot, whereas all Saturn bow shock encounters have a clear overshoot. We find that the ROA of Mercury's bow shock ranges from 0 (no overshoot) to 0.6, with a typical value of 0.2. We find that the ROA of Saturn's bow shock ranges from 0.2 to 5, with a typical value of 2. This clear ROA difference is consistent with the expected lower fast magnetosonic Mach number and lower upstream plasma β at Mercury's bow shock, and we suggest that it is very likely to be primarily caused by the different Mach numbers. This confirmed variation in bow shock parameter regime may produce a different solar wind‐magnetosphere interaction at these two planets. Key Points: Mercury's bow shock has a smaller magnetic overshoot than Saturn's bow shock This is very likely because of the much lower solar wind Mach numbers at Mercury This may produce different solar wind‐magnetosphere interactions